Water quality of the Athabasca oil sands area: A regional study ... - Corkum, L. (University of Alberta Library, 1985)
The objective of this report is to summarize water quality constituents in the AOSERP study area and to examine relationships between these constituents and changes in land formation, hydrology, and development. Summaries of routine parameters, nutrients, and metals are presented for sampling sites along the Athabasca River to detect longitudinal and seasonal changes in water quality and to determine the effects of point source effluents on the river. Changes in ion concentrations on the Athabasca River were attributed to inputs from the Clearwater River rather than industrial saline discharge via Poplar Creek. The downstream effect of the Fort McMurray sewage treatment plant was limited to the mainstem upstream of the confluence with the Muskeg River. Elevated concentrations of nickel and vanadium occurred during high flow periods, indicating that concentrations of these metals in surface waters were associated with weathering of natural bitumen rather than with industrial effluents. A principal component ...